Ocorrência de Aethalion reticulatum Linnaeus (Hemiptera: Aethalionidae) em Tectona grandis Linn. f. (Verbenaceae) em Minas Gerais, Brasil - Tavares, Thiago Assis; Fonseca, Adriano Geraldo; Sousa, Fernanda Freitas; de Assis Júnior, Sebastião Lourenço (EntomoBrasilis, 2018)
Resumo. A Teca (Tectona grandis Linn. F.) é uma espécie arbórea oriunda do sudeste da Ásia que foi introduzida no Brasil nos anos 60. Atualmente seu cultivo está em franca expansão em vários estados. Apesar desta espécie apresentar relativa resistência, alguns insetos têm sido reportados em povoamentos homogêneos, com possibilidades de provocar perdas em sua produção. Foi observada a ocorrência de uma cigarrinha em teca no município de Paulistas, Minas Gerais, Brasil. A espécie Aethalion reticulatum Linnaeus (Hemiptera: Aethalionidae) foi encontrada em galhos e folhas de árvores com três anos de idade. A ocorrência dessa cigarrinha indica a colonização e adaptação por insetos nativos, que futuramente poderão alcançar o status de praga da cultura da teca. Occurrence of Aethalion reticulatum Linnaeus (Hemiptera: Aethalionidae) in Tectona grandis Linn. f. (Verbenaceae) in Minas Gerais, Brazil Abstract. Teca (Tectona grandis Linn. F.) is a tree species originating in Southeast Asia wich was introduced in Brazil in the 1960s. Currently, its cultivation is booming in several states. Although this species shows relative resistance, some insects have been reported in homogenous stands, with possibilities of causing losses in their production. It was observed the occurrence of a spittlebug in teak in the municipality of Paulistas, Minas Gerais, Brazil. The specie Aethalion reticulatum Linnaeus (Hemiptera: Aethalionidae) was found on branches and leaves of three years old trees. The occurrence of this spittlebug indicates colonization and adaptation by native insects, which may eventually reach the pest status of teak culture.